The Correlation Between Stress And Sleep Quality On The Menstrual Cycle Of Female Students At The Faculty Of Health Sciences, Universitas Muhammadiyah Purwokerto - Farah Al Hanif; Vivi Leona Amelia (Proceedings Series on Health & Medical Sciences, 2026)
The menstrual cycle plays an important role in women's reproductive health, yet many experience irregularities influenced by stress and poor sleep quality. Students, particularly female university students, often face high levels of stress due to academic pressures, which, along with inadequate sleep, contribute to menstrual cycle disturbances. A quantitative cross-sectional study was conducted with 347 female students. Data was collected through purposive sampling and analyzed using the Kruskal-Wallis test to assess the differences in stress and sleep quality levels with respect to menstrual cycle regularity. The study found that 61% of respondents with oligomenorrhea (irregular cycles) had moderate stress levels. A significant difference was observed between stress levels and menstrual cycle regularity (p = 0.000). Similarly, 33.4% of respondents with oligomenorrhea had poor sleep quality, and a statistically significant difference was found between sleep quality and menstrual cycle regularity (p = 0.000). Both stress and sleep quality are significantly associated with menstrual cycle irregularities in female students. Interventions aimed at reducing stress and improving sleep quality may help regulate menstrual cycles.